THE LOW COMPETENCY OF EARLY CHILDHOOD EDUCATION TEACHERS INFLUENCES PROFESSIONAL DUTIES - Watini, Sri; Bernarte, Racidon (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The teacher is the determinant in the success of the learning process; it requires teachers who have professional Information Technology (IT) competence. In reality, many teachers have low IT competence. This study aims to determine IT competence for Early Childhood Education teachers in Bekasi, West Java. This research used the Survey Method. The techniques used in data collection are questionnaires and interviews—questionnaire in the form of ten questions that must be filled by respondents. The respondents in this study were 50 Early Childhood Education teachers taken by random sampling. The results of this study show the IT Competence of Early Childhood Education Teachers in Bekasi City is still low, and the need for the policies of certain parties to require Early Childhood Education teachers must have IT competence. Policies that require Early Childhood Education teachers to have comprehensive IT competencies need to be supported by regular monitoring and evaluation to ensure the effectiveness of the IT devices as media in the latest integrated technology learning. The teachers did competence due to the application of IT equipment in Early Childhood Education. They can be in line and contribute positively to the development of children's cognition, psychomotor, and practical. Moreover, Early Childhood Education is the initial phase of a child's formal education.